Investigation of in vivo antipyretic activity of thottea dependens leaves - Ahmed, Qamar Uddin; I, Radhiah; Mat So'ad, Siti Zaiton (IIUM Press, 2015)
Introduction: Leaves of Thottea dependens have been used as folk medicine in Malaysia for the treatment of several conditions involving pain and inflammation with accompanying pyrexia. However, there is no scientific evidence for its effectiveness to treat fever. Hence, the purpose of this study was to evaluate the anti-pyretic activity of methanol (MeOH) and aqueous (Aq) extracts of T. dependens leaves in albino mice (ICR strain). Methods: Thirty-six albino mice of both sexes, randomized into six groups (n=6) were used. Group I served as the control and received only the vehicle, normal saline. Group II received paracetamol 150 mg/kg body weight (b.w.) orally, groups III and IV received 100 and 200 mg/kg b.w. of the MeOH extract while groups V and VI received 100 and 200 mg/kg b.w. of the Aq extract orally. Pyrexia was induced by a subcutaneous injection of 10 mL/kg b.w. of 15% (w/v) yeast suspended in 0.5% (w/v) methylcellulose solution. LD50 of both extracts were determined according to the method of Organisation for Economic Co-operation and Development guidelines. Phytochemical screening was carried out qualitatively for the presence of different class of biologically active compounds. Results: LD50 values for both extracts were found to be greater than 1000 mg/kg b.w. indicating the wide margin of safety of T. dependens leaves. The MeOH extract at 200 mg/kg b.w. showed statistically significant (P<0.01) dose dependent reduction of brewer’s yeast induced pyrexia in albino mice. Flavonoids, saponins and phenolic compounds were found to be major biologically active phytoconstituents in MeOH extract. Conclusion: The study showed that T. dependens leaves possess significant anti-pyretic activity, thus justifying its ethnomedicinal use in Malaysia to treat fever. KEYWORDS: Thottea dependens, Brewer’s yeast induced pyrexia, albino mice